Complete collision data set for electrons scattering on molecular hydrogen and its isotopologues: IV. Vibrationally-resolved ionization of the ground and excited electronic states - Scarlett, Liam; Jong, E.; Odelia, S.; Zammit, M.C.; Ralchenko, Y.; Schneider, B.I.; Bray, Igor; Fursa, Dmitry (2023)
We present a comprehensive set of vibrationally-resolved cross sections for electron-impact ionization of molecular hydrogen and its isotopologues (H2, D2, T2, HD, HT, and DT) in both the ground and excited electronic states. We apply the adiabatic-nuclei molecular convergent close-coupling (MCCC) method to calculate cross sections from threshold to 1000 eV for ionization of the ground and excited vibrational levels of the X1Σg+, B1Σu+, C1Πu, EF1Σg+, a3Σg+, and c3Πu electronic states, representing all states with united-atoms-limit principle quantum number n=1–2. The cross sections are presented in graphical form and provided as both numerical values and analytic fit functions in supplementary data files. The data can also be downloaded from the MCCC database at mccc-db.org.